AEW Diabetic Foot Gymnastics improves foot sensitivity in patients with Type 2 Diabetes Milletus: Diabetic Foot Exercises Increase Foot Sensitivity Patients with Diabetes Mellitus Type 2 - Agnes Wijayanti; Erwinda Yunitrie (Bachelor of Hospital Administration, Faculty of Health Sciences, Universitas Singaperbangsa Karawang, 2024)
Background : Diabetes mellitus is a type of non-communicable disease if left unchecked can lead to complications, one form of which is sensory neuropathy. The treatment that needs to be done is by doing physical exercises in the form of diabetic foot exercises to increase the sensitivity of the feet in patients with diabetes melitus. Objective : Identify the effect of foot exercise on increasing foot sensitivity before and after being given foot exercise. Method : Analytic descriptive case study using a nursing care approach with 2 respondents. Result : There is a big influence on increasing the sensitivity of the feet from respondents 1 of 4 areas that cannot feel the sensation to 1 area that cannot feel the sensation of monofilament. Whereas in respondents 2 of 5 areas cannot feel the sensation to 3 areas cannot feel the sensation of monofilament. Conclusions : After doing foot exercises 3x in 1 week for 30 minutes showed an increase in foot sensitivity